Not-so-expert review… - Robson, Jonathan (Septentrio Conference Series, 2016)
Countless hours are spent writing expert reviews for one reason or another, but how many and what for? How do you write a good review and should you get credit for it? With data from a survey aimed at researchers at Södertörn University, Sweden, we considered what is needed to master this not-so-often-talked-about art form.